2023
DOI: 10.1038/s41388-023-02651-4
|View full text |Cite
|
Sign up to set email alerts
|

Serine/threonine kinase TBK1 promotes cholangiocarcinoma progression via direct regulation of β-catenin

Abstract: Cholangiocarcinoma (CCA) is a highly heterogeneous and metastatic malignancy with a poor prognosis even after curative hepatectomy. Studies exploring its pathogenesis and identifying effective therapeutic targets are urgently needed. In this study, we found that TANK-binding kinase 1 (TBK1), a serine/threonine-protein kinase, showed a dynamic increase during the different stages of murine spontaneous CCA carcinogenesis (hyperplasia, dysplasia, and CCA). TBK1 was upregulated in human tissues, including intrahep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…This activation enhances the immunogenicity of the tumor cells 36 . Furthermore, studies have demonstrated that the serine/threonine kinase TBK1 can promote cholangiocarcinoma progression by directly regulating β-catenin phosphorylation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…This activation enhances the immunogenicity of the tumor cells 36 . Furthermore, studies have demonstrated that the serine/threonine kinase TBK1 can promote cholangiocarcinoma progression by directly regulating β-catenin phosphorylation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…As si-PGK1 reduced β-catenin (Figure 6E), we hypothesized that the PGK1 expressed through NF-κB and p-Tyr42 RhoA could stabilize β-catenin through phosphorylation. Recently, it was reported that chitinase 3-like 1 (Chi3l1) binds to CD44 and induces the phosphorylation of β-catenin at Ser552 by Akt in glioblastomas [28] and TANK-binding kinase 1 (TBK1) in cholangiocarcinomas [29], leading to its nuclear translocation. Additionally, PKA phosphorylates β-catenin at Ser675, preventing ubiquitination and consequently promoting the stabilization of β-catenin [30].…”
Section: Discussionmentioning
confidence: 99%
“…Histology and immunohistochemistry were performed as previously described. 64 The related antibody information is listed in Table S2 . Images were acquired by an Olympus BX51 Fluorescence Microscope (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%